2014
DOI: 10.1148/radiol.14131732
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Whole-Body PET/MR Imaging in Comparison to PET/CT in Pediatric Oncology: Initial Results

Abstract: Pediatric oncologic PET/MR is technically feasible, showing satisfactory performance for PET quantification with SUVs similar to those of PET/CT. Compared with PET/CT, PET/MR demonstrates equivalent lesion detection rates while offering markedly reduced radiation exposure. Thus, PET/MR is a promising modality for the clinical work-up of pediatric malignancies. Online supplemental material is available for this article.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
117
0
10

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 192 publications
(131 citation statements)
references
References 26 publications
4
117
0
10
Order By: Relevance
“…Despite the sometimes large differences between uptake times, most studies came to the conclusion that there was a high positive correlation for all SUV quantification metrics between both exams and that most of the differences were due to the variance in uptake time between both scans [44-48, 50, 51, 53, 54, 57, 59-61, 64]. In only two studies, some scans were performed on the PET/MR scanner first [52,58], and in two studies, all PET/MR scans were performed before PET/CT [49,56]. All other studies had a longer uptake time of 51-120 min (mean 81 min) for the PET/MR scans and showed a slight increase in SUV between both exams.…”
Section: Clinical Studies Comparing Suv Measurements Between Pet/ct Amentioning
confidence: 99%
“…Despite the sometimes large differences between uptake times, most studies came to the conclusion that there was a high positive correlation for all SUV quantification metrics between both exams and that most of the differences were due to the variance in uptake time between both scans [44-48, 50, 51, 53, 54, 57, 59-61, 64]. In only two studies, some scans were performed on the PET/MR scanner first [52,58], and in two studies, all PET/MR scans were performed before PET/CT [49,56]. All other studies had a longer uptake time of 51-120 min (mean 81 min) for the PET/MR scans and showed a slight increase in SUV between both exams.…”
Section: Clinical Studies Comparing Suv Measurements Between Pet/ct Amentioning
confidence: 99%
“…The CT component of a PET/CT scan contributes approximately 73% of the total effective dose unless modern low-dose CT techniques are used (32). However, efforts to decrease CT radiation exposure come at the expense of decreased image quality and anatomic detail.…”
Section: Pet and Prostate Cancermentioning
confidence: 99%
“…The effective dose from PET/MR examination was about 20∼50 % that of PET/CT examinations [72][73][74]. Despite the SUV decrease in bone marrow in PET with MRbased attenuation correction method, lesion detection performance of PET/MR showed comparable to that of PET/CT (61 focal uptakes among 62 focal uptakes on PET/CT) [73]. Single PET/MR examination could result in a potential change of management plan in five of nine patients based on superior soft tissue contrast of MRI than that of CT [74].…”
Section: Othersmentioning
confidence: 99%